Effect Mediation of Green Behaviors on Green Employee Involvement in Improving Job Satisfaction in Pusat Sistem Informasi dan Teknologi Keuangan (PUSINTEK) - Purba, Sylvia Diana; Tikurura, Ritha (KINERJA, 2022)
This study aims to examine the effect of green employee involvement on job satisfaction with green behaviors as am mediating variable. The number of respondents in this study were 265 employees who were in the head office and vertical Pusintek. The data collection was carried out by survey method and using convenience sampling technique. The analytical method used is SEM which is analyzed using the SmartPLS 3.3.2. The results showed that green employes involvement has a direct and significant effect on job satisfaction and green behaviors. And green behaviors have a significant direct effect on job satisfaction. On the other hand, green employee involvement has a significant direct effect on job satisfaction with the mediation of green behaviors.